Advances in Information Technology 5th International Conference, IAIT 2012, Bangkok, Thailand, December 6-7, 2012. Proceedings - Papasratorn, Borworn; Charoenkitkarn, Nipon; Lavangnananda, Kittichai; Chutimaskul, Wichian; Vanijja, Vajirasak; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 5th International Conference on Advances in Information Technology, IAIT 2012, held in Bangkok, Thailand, in December 2012. The 18 revised papers presented in this volume were carefully reviewed and selected from 37 submissions. They deal with all areas related to applied information technology, such as e-service; information and communication technology; intelligent systems; information management; and platform technology.
A Framework of Rights Allocation in Online Social Networks -- COAT: Collaborative Outgoing Anti-spam Technique -- Performance Comparison of Some Hybrid Deadline Based Scheduling Algorithms for Computational Grid -- Challenges to Advanced Electronic Evidence Lifecycle Management in an International Court Environment -- Green Cooperative Transmission Scheme for Estimate-and-Forward Relay Based Wireless Communication Systems -- Multimedia Delivery for Elderly People: A Conceptual Model -- Impact of Voltage Levels Number for Energy-Aware Bi-objective DAG Scheduling for Multi-processors Systems -- Semantic Interpretation of UN/EDIFACT Messages for Evaluating Inter-organizational Relationships -- Design and Implementation of a Secure Online Lottery System -- Optical Music Recognition on Android Platform -- A Reverse Engineering Tool Considering Design Intention for Embedded System -- Growing Art: The Evolutionary Art Tools -- Survey of Smart Technologies for Fall Motion Detection: Techniques, Algorithms and Tools -- Exploiting Cloud Computing in Competence Management: A Pharmacy Case -- An Implementation of a High Capacity 2D Barcode -- Literature Review and Proposed Framework on CAD: Automated Cardiac MR Images Segmentation and Classification -- Perceptual Evaluation of Speech Quality Measurement on Speex Codec VoIP with Tonal Language Thai -- Cultural Difference and Perceived CIO Role Effectiveness in Higher Education in ASEAN.
Keywords: Computer science; Computer network architectures; Software engineering; Data encryption (Computer science).; Artificial intelligence; Computer Science; Software Engineering; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Data Encryption; Computer Systems Organization and Communication Networks